Unethical Issues in Advertising - Verma, Amit (Indian Journal of Marketing, 2011)
In modern times, advertising has been playing a significant role in our socio-economic life. It is considered an effective and cost efficient tool for communication. Though advertising is used for non economic purposes, it is highly used to attain business objectives. In this era of globalization and deregulation, advertising has acquired a new status. Technological advances have added new feathers to the entire gamut of advertising, and hectic competition has made advertising more powerful in the process of attracting and holding customers. As a result, advertising has been the victim of criticisms and abuses. Different social thinkers and other organisations throughout the world express their serious concerns on the role advertising plays. It is normally believed that most of the advertisements today are the embodiment of unethical practices. Most of the advertisements are viewed as offensive, indecent, vulgar, repulsive, and against public decency. More particularly, it affects children negatively. The present paper makes an attempt to examine the attitudes of consumers regarding advertisements. The paper is based on an empirical study with a sample size of 100 respondents consisting of university teachers, students, and the common consumers. Appropriate statistical tools have been used for analysis and interpretation.